Konsep Pelayanan Keperawatan Komplementer Alternatif Dengan Pendekatan Teori Dorothea Orem - Ario Prio Agus Santoso; Cindy Amelia Agustin; Fatihah Balqis Azzahra; Hana Efani; Tito Angelito Coreia; Zalika Hilwa Safitri (Journal of Complementary in Health, 2022)
Nurses as health professionals can participate in complementary therapies that patients can do independently. In this case a nurse has a role as an educator. This study aims to determine the concept of alternative complementary nursing with the Dorothea Orem theory approach. This research method is a literature study conducted by reviewing and analyzing several sources of articles. The results of the study show that the application of alternative complementary nursing care to patients can be done independently in accordance with the concept of Dorothea Orem theory, evidenced by the existence of acupressure therapy, hypnotherapy, herbs, and so on.